2012
DOI: 10.1242/dmm.009233
|View full text |Cite
|
Sign up to set email alerts
|

Elaidyl-sulfamide, an oleoylethanolamide-modelled PPARα agonist, reduces body weight gain and plasma cholesterol in rats

Abstract: SUMMARYWe have modelled elaidyl-sulfamide (ES), a sulfamoyl analogue of oleoylethanolamide (OEA). ES is a lipid mediator of satiety that works through the peroxisome proliferator-activated receptor alpha (PPARα). We have characterised the pharmacological profile of ES (0.3–3 mg/kg body weight) by means of in silico molecular docking to the PPARα receptor, in vitro transcription through PPARα, and in vitro and in vivo administration to obese rats. ES interacts with the binding site of PPARα in a similar way as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
(55 reference statements)
0
21
1
Order By: Relevance
“…In the present study, OEA binding to PPAR-α was stabilized through the formation of hydrogen bouds with Ser280, Tyr314, and Phe273, whereas a previous study reported hydrogen bounding with Ser280 and His440 [26]. This apparent discrepancy may have resulted from differences in model systems; e.g., 1i7g (crystal structure of the ligand binding domain from human PPAR-α in complex with the agonist AZ242) versus 1k7l (crystal structure of the human PPAR-α ligand binding domain bound with GW409544 and a co-activator peptide) [26].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In the present study, OEA binding to PPAR-α was stabilized through the formation of hydrogen bouds with Ser280, Tyr314, and Phe273, whereas a previous study reported hydrogen bounding with Ser280 and His440 [26]. This apparent discrepancy may have resulted from differences in model systems; e.g., 1i7g (crystal structure of the ligand binding domain from human PPAR-α in complex with the agonist AZ242) versus 1k7l (crystal structure of the human PPAR-α ligand binding domain bound with GW409544 and a co-activator peptide) [26].…”
Section: Discussioncontrasting
confidence: 67%
“…This apparent discrepancy may have resulted from differences in model systems; e.g., 1i7g (crystal structure of the ligand binding domain from human PPAR-α in complex with the agonist AZ242) versus 1k7l (crystal structure of the human PPAR-α ligand binding domain bound with GW409544 and a co-activator peptide) [26].…”
Section: Discussionmentioning
confidence: 99%
“…We performed real-time qPCR (TaqMan, Life Technologies) as described previously [48]. Tissue portions (100–300 mg) of the liver, PAT and the whole hypothalamus were homogenized.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in rats OEA regulates several hepatic enzymes including liver fatty acid binding protein (responsible for uptake and intracellular trafficking of fatty acids) [113] and the thermogenic uncoupling protein-1 [114]. Also, subchronic administration of a recently synthesized analog of OEA that binds PPARα receptors, elaidyl-sulfamide, was found to lower plasma cholesterol and improve the hepatic function of obese rats [115]. Clearly, these…”
Section: Oea and The Control Of Energy Homeostasismentioning
confidence: 96%